Thermally decomposed Ni-Fe-hydrotalcite: a highly active catalyst for the solvent-free N-acylation of different amines by acid chlorides - Choudhary, Vasant R.; Dumbre, Deepa K. (Catalysis Communications, 2011)
A composite Ni-Fe catalyst obtained from the thermal decomposition of Ni-Fe-hydrotalcite at 600 degrees C shows very high activity in the solvent-free N-acylation of amines by different acid chlorides with high product yields under very mild reaction conditions (viz, room temperature, short reaction period and small amount of catalyst). The catalyst also shows excellent reusability in the reaction. The crystalline phases present in the catalyst are mixed oxides and hydroxides of nickel and iron. The high catalytic activity of the decomposed Ni-Fe-hydrotalcite is attributed to the formation of uniformly distributed Ni-Fe metal oxides and hydroxides. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Acid chlorides; amines; Decomposition of Ni-Fe-hydrotalcite; N-acylation of amines; Ni-Fe-hydrotalcite derived catalyst